Exploring Lung Histopathology in White Rats After Cigarette Smoke Exposure - Edward Pandu Wiriansya; Asyifah Andari Syarif; Muhammad Naufal Zuhair; Syamsu Rijal; Dzul Ikram; Ismail Ismail; Muhammad Azka Al Atsari; Andi Nurdahlia (Lambung Mangkurat, 2023)
Smoking-induced respiratory epithelium changes, driven by nicotine and smoke components, can lead to severe lung alterations with prolonged exposure. However, until now, no one has examined the histopathological appearance of bronchioles and alveoli in Wistar rats following exposure to cigarette smoke. This study aimed to assessed lung histopathological changes in white rats (Rattus norvegicus) exposed to cigarette smoke. A descriptive study used a post-test group control design, exposing Rattus norvegicus to cigarette smoke and dividing them into control, 1-week, 2-week, and 4-week groups. Histopathological findings revealed that the control group had intact bronchioles; the one-week group showed lymphocyte infiltration and typical alveolar structure; the two-week group had increased respiratory epithelial cells; the four-week group displayed dominant bronchiole changes; the one-week group had varying alveolar septal thickness; the two-week group had narrowed alveolar lumens; four-week group showed thickened septa and pronounced pigmented macrophages. Cigarette smoke exposure affects changes to Rattus norvegicus lung histology. Prolonged exposure to cigarette smoke induces damage to the structure of the bronchioles and alveoli.